2004
DOI: 10.1002/pros.20017
|View full text |Cite
|
Sign up to set email alerts
|

Screening decreases prostate cancer mortality: 11‐year follow‐up of the 1988 Quebec prospective randomized controlled trial

Abstract: Seventy-four (74) deaths from prostate cancer occurred in the 14,231 unscreened controls while 10 deaths were observed in the screened group of 7,348 men during the first 11 years following randomization. Median follow-up of screened men was 7.93 years. A Cox proportional hazards model of the age at death from prostate cancer shows a 62% reduction (P < 0.002, Fisher's exact test) of cause-specific mortality in the screened men (P = 0.005). These results are in agreement with the continuous decrease of prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 42 publications
5
113
0
8
Order By: Relevance
“…10,14 In the ERSPC study, after initial screening, screening was only offered every 4 years or once after 4 years. 25 As a result, after 11 years of follow-up, PSA testing had been done on average only 2.27 times per man over the 11-year period, including first screening for a median interval of 4.02 years between screenings 12 ( Table 1).…”
Section: Psa Screening Intervalmentioning
confidence: 99%
See 3 more Smart Citations
“…10,14 In the ERSPC study, after initial screening, screening was only offered every 4 years or once after 4 years. 25 As a result, after 11 years of follow-up, PSA testing had been done on average only 2.27 times per man over the 11-year period, including first screening for a median interval of 4.02 years between screenings 12 ( Table 1).…”
Section: Psa Screening Intervalmentioning
confidence: 99%
“…Unfortunately, it has been estimated that the PLCO trial had up to 85% of men screened in their 'control' arm, 19 while a 24% contamination was observed in the Rotterdam cohort of the ERSPC 20 and only 7.3% was present in the Quebec study. 14 An interesting observation in the PLCO study, however, is that considering men with no or minimal comorbidity 21 which represented 64% of the total population, the risk of death from prostate cancer was decreased by 44% (P50.03) 21 and 27% (P50.03). 15 Does this mean that men with significant comorbidity did not follow screening and treatment to the same extent as the men in relative good general health?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, a drop in PCa-related mortality has been reported; 3,4 recently, the European Randomized Study of Screening for Prostate Cancer (ERSPC) reported a 20% reduction of mortality in the screened arm with an estimated rate of overdiagnosis as high as 50%. 1 Overdiagnosis and the high prevalence of adverse side effects related to unnecessary treatments make the overall benefit of PSA mass screening unclear.…”
Section: Introductionmentioning
confidence: 99%